2017
DOI: 10.1103/physreve.96.033110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of viscous heating and wall-fluid interaction energy on rate-dependent slip behavior of simple fluids

Abstract: Molecular dynamics simulations are used to investigate the rate and temperature dependence of the slip length in thin liquid films confined by smooth, thermal substrates. In our setup, the heat generated in a force-driven flow is removed by the thermostat applied on several wall layers away from liquid-solid interfaces. We found that for both high and low wall-fluid interaction (WFI) energies, the temperature of the fluid phase rises significantly as the shear rate increases. Surprisingly, with increasing shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…The smaller strength of ε up WL or ε down WL is able to cause intrinsic slip at the fluid-wall interface. According to the previous works, the intrinsic slip length of order 10 σ ( Priezjev and Troian, 2004;Priezjev, 2007;Bao et al, 2017;Hu et al, 2018 ) is comparable to the local slip length at the GLI. In our work, we focus on the situation where the no-slip boundary condition is valid on the fluid-wall interface, and leave the influence of intrinsic slip on the local slip at GLI in the future work.…”
Section: Details Of Molecular Dynamics Simulationsmentioning
confidence: 65%
See 2 more Smart Citations
“…The smaller strength of ε up WL or ε down WL is able to cause intrinsic slip at the fluid-wall interface. According to the previous works, the intrinsic slip length of order 10 σ ( Priezjev and Troian, 2004;Priezjev, 2007;Bao et al, 2017;Hu et al, 2018 ) is comparable to the local slip length at the GLI. In our work, we focus on the situation where the no-slip boundary condition is valid on the fluid-wall interface, and leave the influence of intrinsic slip on the local slip at GLI in the future work.…”
Section: Details Of Molecular Dynamics Simulationsmentioning
confidence: 65%
“…It is well known that for flows over a homogeneous solid surface, the velocity profiles are simply linear and parabolic for Couette and Poiseuille flows, respectively. Correspondingly, the local shear rate can be obtained by fitting the velocity profile in the bulk region and then extrapolating the fitting curve with respect to the solid-liquid interface ( Lichter et al, 2004;Priezjev and Troian, 20 04;Priezjev, 20 07;Liu and Li, 2010;Bao et al, 2017 ). However, for a liquid flowing over SHS, the presence of GLI perturbs the flow field, which leads to spatially varying velocity profiles near the GLI ( Schnecker et al, 2014 ).…”
Section: The Local Slip Length In Transverse and Longitudinal Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their values are obtained by build in command in Mathematica while we have used self-coded algorithm (shooting method with R-K scheme) subject to Casson nanofluid flow induced by solid rotating disk. Beside this one can extend idea to computational fluid dynamics in context of industrial and standpoints, see References [32][33][34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of boundary slip are of interest, but there is still no clear understanding of the slip. Previous studies found that surface wettability is a possible reason to affect slip, however, the effect of wettability on slip can be complex and both hydrophobic and hydrophilic surface can induce either slip or no-slip boundary condition, which is dependent on the strength of solid-liquid interface [ 14 , 15 , 16 , 17 , 18 ]. Additionally, surface roughness including texture spacing and texture height can also significantly affect the degree of slip [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%